Development of Nanoemulsions for Wound Dressings Containing Cassia alata L. Leaf Extraction - Surat Sangkaew; Smith Wanmasae; Kingkan Bunluepeuch; Tassanee Ongtanasup; Siriwan Srisang; Chawan Manaspon; Philaslak Pooprommin; Komgrit Eawsakul (Evidence-based Complementary and Alternative Medicine, 2022)
drug release profile indicated that the A/P created a regulated drug release profile, and the cell viability experiment revealed that the film was nontoxic and hemocompatible. A/P composite films can be produced using CAN extract as a possible wound dressing. However, further studies in animals and humans are required to determine both safety and effectiveness.
Keywords: Phytochemistry and biological activity of medicinal plants; Natural Compounds in Disease Treatment; Polysaccharides and Plant Cell Walls